Synthesis, Characterization and X-Ray Crystal Structure of Dizinc(II) Complex of Pseudo Calixarene Macrocycle Based on 2,2-Methylene-bis[(6-formyl)-4-tert-butylphenol] and 1,3-Diamino-2-propanol - Hussain, Imdad; Gillani, Rubina; McKee, Vickie; Kose, Muhammet; Ali, Zulfiqar; Hussain, Habib (Asian Journal of Chemistry, 2015)
[(2+2)Zn2·CH3COO] complex was prepared by refluxing 2,2-methylene-bis[(6-formyl)-4-tert-butylphenol] (H2mftbp) and 1,3-diamino-2-propanol in a round-bottomed flask containing Ca(ClO4)2 in ethanol in the presence of a base. Sample was taken from the refluxing solution and submitted for MS. ESI-MS showed the peak to confirm the formation of calcium complex [(2+2)Ca] but when Zn(CH3COO)2·2H2O was added and refluxed for further 6 h. Zinc replaced calcium metal and a new complex of Zn was formed as [Zn2(2+2)] complex. A yellow powder was filtered after cooling at room temperature. The powder was crystallized by vapour diffusion method. The complex crystallizes in the monoclinic crystal system with space group P2(1)/n. Unit cell parameters are; a = 13.6595(7) Å, b = 18.5216(9) Å, c = 25.0723(12) Å, a = 90°, b = 95.7020(10)°, g = 90°, Z = 8 and V= 6311.8(5) Å3. The complex was characterized by using single crystal X-ray spectroscopy, IR-spectroscopy and ESI-mass spectrophotometery.